A Cushing's syndrome patient's severe insomnia and morning blood pressure surge both improved after her left adrenal tumor resection. Issue 6 (December 2016) - Imaizumi, Yuki; Ibaraki, Ai; Asada, Satoshi; Tominaga, Mitsuhiro; Hayashi, Hiroyuki; Tsuchihashi, Takuya; Eguchi, Kazuo; Kario, Kazuomi; Taketomi, Akira
Abstract : Underlying mechanisms of the elevated risks of hypertension and cardiovascular disease (CVD) in Cushing's syndrome (CS) are unclear. We treated an adult woman with CS because of a cortisol-secreting adrenal tumor. After tumor resection, the 24-h blood pressure (BP) level improved from 156/91 to 131/84 mmHg; the morning BP surprisingly improved from 174/98 to 127/93 mmHg, although we reduced her antihypertensive medication. Her sleep quality (by the Pittsburgh Sleep Quality Index) improved from 7 to 2 points. Disturbed circadian BP rhythm is often observed in CS, but was reported only as altered nocturnal BP fall. This is the first report showing the disappearance of the morning BP surge evaluated by ambulatory BP monitoring with postsurgery sleep quality improvement. Poor-quality sleep, followed by exaggerated morning BP surge may thus be a cause of CS-related cardiovascular events. Sleep quality and BP circadian rhythm evaluations may clarify hypertension and high CVD risk in CS.